Analysis of mutation in human cells by using an Epstein-Barr virus shuttle system. - DuBridge, R B (1987)
We developed highly sensitive shuttle vector systems for detection of mutations formed in human cells using autonomously replicating derivatives of Epstein-Barr virus (EBV). EBV vectors carrying the bacterial lacI gene as the target for mutation were established in human cells and later returned to Escherichia coli for rapid detection and analysis of lacI mutations. The majority of the clonal cell lines created by establishment of the lacI-EBV vector show spontaneous LacI- frequencies of less than 10(-5) and are suitable for studies of induced mutation. The ability to isolate clonal lines represents a major advantage of the EBV vectors over transiently replicating shuttle vectors (such as those derived from simian virus 40) for the study of mutation. The DNA sequence changes were determined for 61 lacI mutations induced by exposure of one of the cell lines to N-nitroso-N-methylurea. A total of 33 of 34 lacI nonsense mutations and 26 of 27 missense mutations involve G X C to A X T transitions. These data provide support for the mutational theory of cancer.